Factors constraining and enabling the adoption of a disruptive technology by African small, micro, and medium enterprises for the Fourth Industrial Revolution: The case of mobile money - Tarr, Dillon (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
The Fourth Industrial Revolution (4IR) is set to disrupt existing economic and social structures through the use of cyber-physical systems that result from a fusion of the digital, biological, and physical spheres. The fifth and current long wave of innovation is going through such a digital revolution in the ongoing deployment period which is being driven by the generalpurpose technologies of Artificial Intelligence and the Internet of Things, among other cyberphysical systems. The impact of mobile money in the access of financial services has shown how disruptive incremental innovations in mobile and digital technologies can be. The transformational power of mobile money in financial access is due to its use as an accessible financial tool that utilizes mobile devices to send and/or receive money over great distances. With the 4IR looming, this thesis determines the factors that enable and constrain the adoption of a disruptive technology amongst Sub-Saharan African small, micro, and medium enterprises (SMMEs). Therefore, due to its impact on financial inclusion and the formalization of SMMEs, mobile money is used as an indicator for the adoption of 4IR disruptive digital technologies. The adoption of mobile money was evaluated using secondary data from a survey conducted by Research ICT Africa, which surveyed 4408 SMMEs in nine African countries. The Diffusion of Innovations (DOI) model and the Unified Theory of Acceptance and Use of Technology (UTAUT) model were used to identify the factors enabling and constraining the adoption of a disruptive technology, in this case mobile money. Factors included gender, vocational training, business skills training, tertiary education, services, performance expectancy, social media, location, and nine African countries (Kenya, Mozambique, Ghana, Nigeria, Rwanda, South Africa, Tanzania, Uganda, and Senegal). The factors were grouped into owner characteristics, firm attributes and country attributes. SMME owners with business skills (49%) showed the highest level of adoption in terms of owner characteristics, Kenyan SMMEs (21%) had the highest adoption between the countries surveyed, and social media (62%) showed the highest adoption in terms of firm attributes followed by the formal variable (47%). In general, only 29% of SMMEs surveyed adopted mobile money. The study found that women SMME owners were more likely to be affected by business formality when adopting a disruptive technology compared to male owned SMMEs. This is because informality often exacerbates other barriers/challenges women face such as lower access to finance, lower ability to exercise property, business, and labour rights, and lower visibility. The results also demonstrate that vocational training is more important than general tertiary education for the ii adoption of a disruptive technology such as mobile money. Furthermore, when using social media as a tool for business advice SMME owners were more likely to adopt the disruptive technology. The study suggests that to encourage African SMMEs to adequately adopt disruptive technologies of the 4IR, more women owned SMMEs need to enter the formal economy, and vocational training targeted at business skills must be promoted amongst all SMME owners. Eastern African SMMEs were found to be more likely to adopt mobile money compared to other African regions. The finding demonstrates the need for more African countries (particularly outside of the Eastern African region) to encourage innovation by addressing the four enablers of mobile connectivity (i.e. infrastructure, affordability, consumer readiness, and mobile services) which will in effect lead to economic growth and development. The study shows that to address country/regional differences, in addition to building the required infrastructure in terms of mobile internet connectivity, countries should increase the local relevancy of disruptive technologies between SMMEs. To achieve this the study suggests increasing mobile social media penetration rates. This is because when social media is used as a tool for business advice SMME owners are more likely to adopt a disruptive technology (as is the case with mobile money) due to the social influence of social media.
Keywords: Disruptive technologies; Mobile commerce; Industry 4.0; Small business Africa, Sub-Saharan; Diffusion of innovations Africa, Sub-Saharan; Technological innovations -- Management